A study on the space programming, anthropometrics and ergonomics of Fire Stations in Davao City to improve the efficiency and safety of the fire personnel - Israel, Val Lois Gosimvino L. (2014)
The nature of work firemen needs no lengthy explanation. Their duty requires them to be always alert to respond to fire alarms or assist other local government units in need. Moreover, when emergency arises the movement of people within the station should be fast and efficient that would enable them to respond in the shortest time possible. However, if there are space constraints or improper work flow within the station such goal might not be attained and injury would not be avoided. This research uses the principles of ergonomics, coupled with study of anthropometrics and space-programming in order to create an efficient workspace for the firemen of Davao City. This study validates the variables already known in the creation and structure of current fire station and applies the principles aforementioned above. Thus, this research will contribute further to understanding the role of building a fire station that considers its personnel and their nature if work and the structure?s physical condition.